Anthropological Investigations of late heathen graves in Upernavik District. - Balslev Jørgensen, J.; Vesely, M.; Fennow, Karin (Meddelelser om Grønland, 1974)
The Eskimos came to Greenland in several waves, each group carrying with it its own culture. Skeletal materials are however only available from the lnugsuk Culture, the latest culture period. As already mentioned, the investigations of the skeletal materials described above primarily concern the lnugsuk people as they were like shortly after immigrating to Greenland. Their contact with white men essentially takes place during the last two centuries, and coincides with the introduction of Christianity. Thus, by analyzing the skeletal remains of the last heathen Greenlanders, one arrives at a picture of the development of the Inugsuk people throughout half a millenium in Greenland, and at the same time has a basis of comparison between the last pure Eskimos and the present-day Greenlanders. Several investigations of the physical anthropology of these immigrated peoples have already been published ( JØRGENSEN, 1954; LAUGHLIN & JØRGENSEN, 1956; SKELLER, 1954; GESSAIN, 1960).